BUSINESS COMBINATION STRATEGY TO ENHANCE COMPANY COMPETITIVE ADVANTAGE - Wicaksono, Amellia Agustin (International Conference On Economics Business Management And Accounting (ICOEMA), 2025)
This article explores the implementation of hybrid strategy as an approach to enhance competitive advantage amid dynamic and uncertain market conditions. The strategy integrates cost efficiency and product differentiation simultaneously, enabling companies to reach broader market segments without compromising quality and added value. Using a descriptive qualitative approach, this study analyzes literature and case studies from manufacturing and FMCG companies that have successfully applied this strategy. The findings indicate that hybrid strategy enhances operational efficiency, strengthens innovation, and fosters sustainable customer loyalty. Furthermore, it supports business sustainability from both social and environmental perspectives. Thus, hybrid strategy is not merely an alternative but a holistic strategic solution in addressing competitive challenges and digital transformation